As implicações do anticomunismo na indústria cinematográfica hollywoodiana (1947-1950) - Pavani, Luana Casemiro (2025)
This article derives from a master's research project, which is currently in progress, and aims to analyze the role of US policies in the intensification of anti-communism in the Hollywood film industry. Considering the time frame established (1947-1950), the objective was to discuss the relationship between the beginning of the Cold War and the implementation of anti-communist policies in film productions. The methodology used in the dissertation is wide-ranging and includes both bibliographical research and political speeches, official government documents and newspaper and magazine articles. In this article, we will give priority to the  bibliographical research. This article is structured in order to highlight the measures of repression and censorship that were part of Hollywood, as well as to verify the participation of foreign countries in these projects.